Evaluation of Risk Behavior in Gambling Addicted and Opioid Addicted Individuals - Gorzelańczyk, Edward J.; Walecki, Piotr; Błaszczyszyn, Monika; Laskowska, Ewa; Kawala-Sterniuk, Aleksandra (Frontiers in Neuroscience, 2021)
Evidence suggests that both opioid addicted and gambling addicted individuals are characterized with higher \textcolor{red}{levels} of risk behavior in comparison to healthy people. It has been proven that the administration of substitution drugs can reduce craving for opioids and the risky decisions among opioid addicted individuals. Although, it is suggested that the neurobiological foundations of addiction are similar, it is possible that risk behaviors in opioid addicts may differ in detail from those addicted to gambling. The aim of this work was to compare the level of risk behavior in opioid addicted individuals with gambling addicted individuals using Iowa Gambling Task (IGT). The score and response time during the task were measured. It was also observed on the basis of the whole IGT test that gambling addicted individuals take more risk decisions in comparison to healthy individuals from control group but less risk decisions in comparison to opioid addicted individuals before administration of methadone and without any statistically significant difference after administration of methadone, as there has been a growing evidence that methadone administration is strongly associated with a significant decrease in risky behavior.